Impact of succession planning practices on the profitability of Nepalese commercial banks - Simkhada, Aakriti (International Journal of Emerging Trends in Social Sciences, 2023)
This study examines the impact of succession planning practices on the return on assets (RoA) of Nepalese commercial banks. The RoA was taken from the annual report of 20 commercial banks for the year 2020. Structured questionnaires were administered to examine the opinions of the respondents regarding succession planning practices. This study has employed descriptive and causal comparative research designs to deal with the fundamental issues associated with the various influencing factors of succession planning in Nepalese commercial banks. The total number of observations for the study consists of 140 respondents mainly working in the human resource department of those banks. The regression model is estimated to test the significance and effect of succession planning practices on profitability. The study revealed that human resource planning, succession planning, training and development, job rotation and organization culture have positive impact on return on assets. It indicates that higher the human resource planning, succession planning, training and development, job rotation and organization culture higher will be the RoA. However, favoritism and nepotism have a negative impact on return on assets. It implies that increase in favoritism and nepotism in an organization leads to decrease in return on assets. The study concluded that succession planning is very important to increase the level of profitability of Nepalese commercial banks. The study identified that out of six independent variables only job rotation and organization culture have significant and positive association with RoA in Nepalese commercial banks.